Attitudes of Mental Health Workers Towards Early Interventions in Psychiatry: A National Survey. Issue 10 (October 2015) - Ghio, Lucio; Respino, Matteo; Murri, Martino Belvederi; Cocchi, Angelo; Meneghelli, Anna; Amore, Mario; Natta, Werner
Abstract : Abstract: Early intervention (EI) is an effective strategy to improve outcomes of psychiatric disorders, but there is little evidence on mental health professionals' opinions on this approach. Hence, during conferences on this topic, we surveyed participants on the benefits, aims, and barriers to implementation of EI. Participants reported that the most important outcomes of EI were decreasing the risk of long-term social consequences, of severe psychopathological conditions, and chronicization. EI would primarily need to be implemented in the care of psychotic, eating, and mood disorders, whereas the main barriers to EI implementation were the lack of funding and of a prevention-oriented culture. Although these results might be biased by a generic attitude favoring EI, participants showed a very positive attitude towards EI and stated the need of a culture shift towards a more prevention-oriented model in a mental health setting.